2020
DOI: 10.3390/ijerph17134737
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cattle Manure by Anaerobic Co-Digestion with Food Waste and Pig Manure: Methane Yield and Synergistic Effect

Abstract: The management of cattle manure (CM) has become increasingly challenging because its production continues to rise, while the regulations on manure management have become increasingly stringent. In Korea, most farms produce CM as a dry mixture with lignocellulosic bedding materials (mainly sawdust), making it impractical to treat CM by anaerobic digestion. To address this problem, this study examined whether anaerobic co-digestion with food waste (FW) and pig manure (PM) could be an effective approach f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Rice residues in the form of RS have the highest C/N ratio (44.0–74.0) [ 172 ] in comparison with water hyacinth (12–42) [ 173 ], cow manure (24.3) [ 174 ] and pig manure (10.95) [ 175 ]. In the AD process, an optimal C/N ratio in the range of (20–30/1) is needed for bacterial activities.…”
Section: Valorization Of Rice Residuesmentioning
confidence: 99%
“…Rice residues in the form of RS have the highest C/N ratio (44.0–74.0) [ 172 ] in comparison with water hyacinth (12–42) [ 173 ], cow manure (24.3) [ 174 ] and pig manure (10.95) [ 175 ]. In the AD process, an optimal C/N ratio in the range of (20–30/1) is needed for bacterial activities.…”
Section: Valorization Of Rice Residuesmentioning
confidence: 99%
“…The assumption considered additive effects in methane production disregarding synergistic effects, which would lead to better results due to the higher gas obtained and lower volume of digestate needing final disposal. Different authors have widely reported synergistic effects when evaluating mixtures of manures and carbon-rich content substrates [87][88][89][90]. Therefore, the remaining amount of solids in the digested slurry should not be significantly affected.…”
Section: Scenariomentioning
confidence: 99%
“…The accumulated biogas was quantified as approximately 72.6, 659, 647, and 741 L in the inoculation, startup, and stabilization phases (two batches), respectively. Baek et al [36] found that the biochemical methane potential of the cattle manure though mono-digestion can produce around 109.2 L/kgVS. These same researchers concluded that co-digesting cattle manure with food waste and pig manure proved effective in accelerating the initiation of anaerobic digestion, which suggested that the co-digestion strategy could be applied to promote the start-up of a digester to treat cattle manure.…”
Section: Inoculation Start-up and Stabilization Of The Anaerobic Reactor With CMmentioning
confidence: 99%